2004
DOI: 10.3171/foc.2004.17.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic placement of an inferior vena cava filter in high-risk patients undergoing spinal reconstruction

Abstract: Object The purpose of this study was to evaluate the safety and efficacy of prophylactic inferior vena cava (IVC) filter placement in high-risk patients who undergo major spine reconstruction. Methods In the pilot study, 22 patients undergoing major spine reconstruction received prophylactic IVC filters. These patients were prospectively followed to evaluate complications related to the filter, the rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 71 publications
1
36
0
Order By: Relevance
“…In a randomized study looking at the efficacy of different compression devices, including a subgroup of cases receiving coumarine anticoagulation, Rokito et al [12] found a very low DVT rate (0.3%) and no symptomatic PE. In contrast, Rosner et al [13], using a retrospective cohort of high-risk patients as a control group to study the routine use of IVCF as a form of thromboembolic prophylaxis, found a much higher rate of PE (13.1%). Nevertheless, their group was not representative of the average spinal practise and for that reason their findings were not included in our statistic describing the average incidence of PE from the literature (see Table 2).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a randomized study looking at the efficacy of different compression devices, including a subgroup of cases receiving coumarine anticoagulation, Rokito et al [12] found a very low DVT rate (0.3%) and no symptomatic PE. In contrast, Rosner et al [13], using a retrospective cohort of high-risk patients as a control group to study the routine use of IVCF as a form of thromboembolic prophylaxis, found a much higher rate of PE (13.1%). Nevertheless, their group was not representative of the average spinal practise and for that reason their findings were not included in our statistic describing the average incidence of PE from the literature (see Table 2).…”
Section: Discussionmentioning
confidence: 97%
“…DVT incidence has been reported to range from 0% [12] to 15.5% [11] with PE incidence varying from 0% [12] to 13.1% [13]. Although DVT has been studied extensively in the context of spinal surgery, symptomatic PE, which in itself is life threatening, has been given less attention.…”
Section: Introductionmentioning
confidence: 99%
“…Ozturk et al reported a significant decrease in PE risk in their study on 129 patients with similar characteristics (24). In the literature, there are case series, performed on a lower number of patients, pointing to the use of vena cava filters in patients subjected to complex spinal surgery as a safe and effective method in preventing PE (8,20,28). In the present study, pulmonary embolism was not reported in both groups.…”
Section: Akmangit I Et Al: Vena Cava Filter Versus Low Molecular Weimentioning
confidence: 40%
“…Pharmacological agents might result in catastrophic complications in the peri-and postoperative period and their use is therefore not considered to be beneficial (1,6,7,23,18,19). Although absolute and relative indications of vena cava filters are still debatable, their prophylactic use in patients with neurosurgical problems has not been reported thoroughly in the literature (8,10,20,22,24,26,28).…”
Section: Introductionmentioning
confidence: 99%
“…Because of her high risk of VTE recurrence, we elected to place a temporary IVC filter for perioperative VTE protection. [11][12][13] Safety and timing of filter retrieval has been an area of growing concern in the medical literature. A wide array of pathophysiological and social obstacles are faced by physicians in these cases, negatively impacting filter retrieval rates.…”
Section: Discussionmentioning
confidence: 99%